Free school meals policy: how are they governed? comparing India, the USA, Japan, and South Korea - Aldrin Pasha, Julian; Mauludi, Teuku Harza; Imam, Muhammad; Muhyidin, Ali (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Free school meals policy have been implemented globally as a mechanism to promote academic and nutritional equity. This study critically examines the management and challenges of free meal programs in four major countries: India, the USA, Japan, and South Korea. Through a comparative analysis, this article evaluates the governance structures of the programs. The study identifies a range of challenges faced by each country, including logistical complexities, socio-cultural barriers, and economic constraints. Despite their differences, the findings emphasize the importance of strong governance networks, sustained collaboration among key stakeholders—such as government agencies, educational institutions, and local communities—and context-specific policy adaptations. These elements are essential for overcoming challenges and ensuring the effectiveness and sustainability of free school meal policy initiatives. While addressing the primary objectives of health and education, these programs can contribute to broader social benefits.